Sustainable development of a company: building of new level relationship with the consumers of XXI century - Yuriy Bilan (Amfiteatru Economic Journal, 2013)
The article contains a brief description of the concept of sustainable development along with review of the literature considering the aspects of the organizations' responsibility towards consumers. Empirical research focusing on the issues connected with the existence or non-existence of the consumer of the XXI century is presented in the article. Research was conducted through examination of the current business behavior of the companies originating from Croatia, Poland and Ukraine; it covered 500 respondents from the companies operating in different business sectors. Results of the research showed that the concept of sustainable development continuously develops, the companies feel the influence of the shift in the consciousness of the modern consumers and are ready to change in order to comply with their expectations, they aspire to comply with the concept of the sustainable development because such compliance provides them with real economic benefits and building of the new level relationship with the consumers of the XXI century is one of the key factors of such development.
Keywords: D22; F63; 330; sustainable development; organizations' responsibility; consumer awarness; relationship between companies and consumers; business behavior